Deployable ultrasound applicators for endoluminal delivery of volumetric hyperthermia - Muhammad Zubair; Matthew S. Adams; Chris J. Diederich (International Journal of Hyperthermia, 2021)
Purpose To investigate the design of an endoluminal deployable ultrasound applicator for delivering volumetric hyperthermia to deep tissue sites as a possible adjunct to radiation and chemotherapy. Method This study considers an ultrasound applicator consisting of two tubular transducers situated at the end of a catheter assembly, encased within a distensible conical shaped balloon-based reflector that redirects acoustic energy distally into the tissue. The applicator assembly can be inserted endoluminally or laparoscopically in a compact form and expanded after delivery to the target site. Comprehensive acoustic and biothermal simulations and parametric studies were employed in generalized 3D and patient-specific pancreatic head and body tumor models to characterize the acoustic performance and evaluate heating capabilities of the applicator by investigating the device at a range of operating frequencies, tissue acoustic and thermal properties, transducer configurations, power modulation, applicator positioning, and by analyzing the resultant 40, 41, and 43 °C isothermal volumes and penetration depth of the heating volume. Intensity distributions and volumetric temperature contours were calculated to define moderate hyperthermia boundaries. Results Parametric studies demonstrated the frequency selection to control volume and depth of therapeutic heating from 62 to 22 cm3 and 4 to 2.6 cm as frequency ranges from 1 MHz to 4.7 MHz, respectively. Width of the heating profile tracks closely with the aperture. Water cooling within the reflector balloon was effective in controlling temperature to 37 °C maximum within the luminal wall. Patient-specific studies indicated that applicators with extended OD in the range of 3.6–6.2 cm with 0.5–1 cm long and 1 cm OD transducers can heat volumes of 1.1–7 cm3, 3–26 cm3, and 3.3–37.4 cm3 of pancreatic body and head tumors above 43, 41, and 40 °C, respectively. Conclusion In silico studies demonstrated the feasibility of combining endoluminal ultrasound with an integrated expandable balloon reflector for delivering volumetric hyperthermia in regions adjacent to body lumens and cavities.